Analisis Dampak Fenomena El Niño terhadap Produktivitas Kopi di PTPN 1 Regional 5 Kebun Banjarsari Afdeling Rayap - Arifah Zahro Fauziyah (Fakultas Pertanian, 2026)
El Niño is a global climate phenomenon that affects rainfall variability and agricultural productivity, especially in rainfed plantation systems. This study aimed to describe the characteristics of coffee productivity and rainfall during Normal and El Niño years, and to analyze the logistic regression relationship between Sea Surface Temperature (SST) anomalies with coffee productivity and rainfall at PTPN 1 Regional 5 Banjarsari Plantation, Rayap Division, Jember Regency. Secondary data consisted of coffee productivity, rainfall, rainy days, and SST anomalies from 2011 to 2025. Climate conditions were classified into Normal, El Niño, and La Niña years, but the main analysis only used Normal and El Niño years. The results showed that coffee productivity fluctuated during the observation period. The median productivity in Normal years was 398 kg/ha, while in El Niño years it decreased to 262 kg/ha, indicating a decline of approximately 34%. Rainfall also showed annual variation, with a median of 4,210.5 mm/year in Normal years and 4,669 mm/year in El Niño years, showing an increase of approximately 10.9%. Logistic regression analysis showed that SST anomalies explained 13% of coffee productivity variation and 8.6% of rainfall variation. These values indicate that SST anomalies had limited explanatory ability. Coffee productivity and rainfall in the study area were likely influenced by other factors, such as rainfall distribution, rainy days, plant age, phenological phase, soil conditions, and plantation management.
FINALISASI oleh Arif 2026 Juni 18
Keywords: El Niño; Rainfall; Coffee Productivity; Climate Variability; ENSO